PENGUATAN SIKAP MODERAT SANTRI UNTUK MEMBENDUNG GERAKAN RADIKALISME - Wiyono, Ahmad (Dewan Pendidikan Pamekasan, 2024)
The threat of acts of terror in the archipelago remains a frightening specter, in recent years acts of radicalism using violent instruments have occurred in several regions in Indonesia. Ironically, the series of terror acts that occurred in Indonesia (and even in other parts of the world) are always linked to Islam, it is claimed that the perpetrators of the terror were entirely the work of Muslims. So the face of Islam in the world has deteriorated. Islam never teaches violence. For this reason, concrete steps are needed to eradicate radicalism cells in all walks of life, including in the world of Islamic boarding schools. In recent times, concerns have emerged that radicalism movements have begun to penetrate Islamic boarding schools, of course with various methods used by missionaries. This issue may seem trivial, but if left unchecked, an epidemic of radicalism may mushroom in the world of Islamic boarding schools. Responding to this problem, Islamic boarding schools need to strengthen the moderate character of the students by providing a certain amount of knowledge and understanding that is rooted in a culture of tolerance in action, so that beliefs and attitudes of tolerance can go hand in hand and do not prioritize the instruments of violence in responding to the dynamics of life which is full of diversity. The strategy for forming a moderate attitude among students to stem the movement of radicalism is carried out in several ways, first: through a formal approach, namely creating a special curriculum for each learning activity which contains material about the dangers of radicalism, the factors that cause the birth of radicalism, as well as steps to avoid it. Second; a social-moral approach through interaction patterns, namely introducing students to several people who have different religious, cultural, and national backgrounds, so that it is strengthened in the souls of the students that they are both human beings, and there is no reason to hate each other. This is the key to tolerance.